Infection of Brachiella thynni (Copepoda, Lernaeopodidae) on pacific bluefin tuna, Thunnus orientalis (Actinopterygii, Scombridae), cultured in Japan. - Nagasawa, K. (Crustaceana (Leiden), 2015)
In Japan, many species of marine ﬁsh are cultured in coastal waters, and to date 20 species of parasitic copepods have been reported from these ﬁsh: they are mostly caligids (12 spp.), followed by lernaeopodids (4 spp.), pennellids (1 sp.), chondracanthids (1 sp.), taeniacanthids (1 sp.), and an unidentiﬁed species (1 sp.) (Nagasawa, 2015). Since the 1990s, Paciﬁc blueﬁn tuna (Thunnus orientalis (Temminck & Schlegel, 1844)) (Scombridae) has been commercially cultured in southwestern Japan using net cages (Yamamoto, 2012), but due to the short time period of their culture, little information is available on the parasitic copepods infecting farmed T. orientalis. Only a caligid, Caligus macarovi Gusev, 1951, is known to occur on farmed T. orientalis in Japan (Nagasawa, 2011a, b). Recently, a lernaeopodid, Brachiella thynni Cuvier, 1830, was found infecting a net-caged T. orientalis. A single specimen of B. thynni was collected from the body surface near the base of the right pectoral ﬁn of an individual of T. orientalis (2070 g in body weight (BW)) farmed in the western North Paciﬁc Ocean off Miyazaki Prefecture, eastern Kyushu, on 27 February 2013. The copepod specimen was ﬁxed and preserved in 70% ethanol. It is deposited in the Crustacea (Cr) collection of the National Museum of Nature and Science, Tsukuba City, Ibaraki Prefecture, Japan (NSMTCr 24118). The scientiﬁc and common names of ﬁsh used in this paper follow Froese & Pauly (2015).